The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s13287-015-0110-5
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based analysis of progerin expression reveals mitochondrial dysfunction, reactive oxygen species accumulation and altered proteostasis

Abstract: IntroductionNuclear accumulation of a mutant form of the nuclear protein Lamin-A, called Progerin (PG) or Lamin AΔ50, occurs in Hutchinson-Gilford Progeria Syndrome (HGPS) or Progeria, an accelerated aging disease. One of the main symptoms of this genetic disorder is a loss of sub-cutaneous fat due to a dramatic lipodystrophy.MethodsWe stably induced the expression of human PG and GFP -Green Fluorescent Protein- as control in 3T3L1 cells using a lentiviral system to study the effect of PG expression in the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 66 publications
(68 reference statements)
0
38
0
Order By: Relevance
“…Lack of proper mitochondrial replenishment leads to reactive oxygen species (ROS) accumulation in mitochondria derived from oxidative metabolism, inducing cellular damage. Indeed, HGPS patients display an increase in ROS, altered energy generation, and elevated genomic instability markers[22]. Our studies raise the possibility that at least some of the defects observed in PS are derived from abnormal transport of RNAs that are required to sustain mitochondrial replenishment.…”
Section: Resultsmentioning
confidence: 86%
“…Lack of proper mitochondrial replenishment leads to reactive oxygen species (ROS) accumulation in mitochondria derived from oxidative metabolism, inducing cellular damage. Indeed, HGPS patients display an increase in ROS, altered energy generation, and elevated genomic instability markers[22]. Our studies raise the possibility that at least some of the defects observed in PS are derived from abnormal transport of RNAs that are required to sustain mitochondrial replenishment.…”
Section: Resultsmentioning
confidence: 86%
“…The implication of de-regulation of the metabolism in accelerated aging has been also demonstrated. HGPS is characterized by a dramatic lipodystrophy [ 23 ] and has been recently associated to increased protein synthesis [ 15 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, aging is accompanied by a set of hallmarks [ 11 ]. Among them, cellular senescence [ 12 ] mitochondrial dysfunction (13) [ 13 ], stem cell exhaustion [ 14 ], loss of proteostasis [ 15 ] and genomic instability [ 16 ] are the most characteristic. Aging is now considered a multi-factorial process.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative differential proteomic analysis of experimental and clinical samples using isobaric tags for relative and absolute quantification (iTRAQ) or tandem mass tagging TMT multiplex labeling, one of the stable isotope labeling-based proteomic methods using LC-MS/MS, and bioinformatics analysis, are powerful methodologies for identifying novel networks and/or pathways important in biological processes/events and diseases [ 23 , 24 , 25 , 26 ]. These proteomic approaches are also currently becoming important tools for identifying biomarkers and host proteins involved in the pathogenicity and immune responses following viral infections [ 27 , 28 , 29 , 30 ]. The significance of using these proteomic approaches to evaluate the safety of virus vaccines is emerging as well [ 31 ].…”
Section: Introductionmentioning
confidence: 99%